Finance and Macroeconomic Volatility - Denizer, Cevdet; Iyigun, Murat F.; Owen, Ann L. (World Bank, Washington, DC, 2014)
Countries with more developed financial sectors, experience fewer fluctuations in real per capita output, consumption, and investment growth. But the manner in which the financial sector develops matters. The relative importance of banks in the financial system is important in explaining consumption, and investment volatility. The proportion of credit provided to the private sector, best explains volatility of consumption, and output. The authors generate their main results using fixed-effects estimates with panel data from seventy countries for the years 1956-98. Their general findings suggest that the risk management, and information processing provided by banks, maybe especially important in reducing consumption, and investment volatility. The simple availability of credit to the private sector, probably helps smooth consumption, and GDP.